In-situ shear exfoliation and thermal conductivity of SBS/Graphite nanoplatelet nanocomposites. (15th September 2020) - Wen, Yingfeng; Xue, Yang; Li, Xiaojing; Pei, Huijie; Zhou, Xingping; Feng, Yuezhan; Ye, Yunsheng; Xie, Xiaolin; Mai, Yiu-Wing
Abstract: Rapid developments of miniaturization and integration of modern electronic devices have been accompanied by increasing power density, which bring about urgent demands for polymer-based thermal interface materials (TIMs) with efficient thermal conductive properties. However, poor dispersibility of thermal conductive nano-fillers severely limits further improvement in the thermal conductivity of TIMs. Herein, poly(styrene- b -butadiene- b -styrene) (SBS)/graphite nanoplatelet (GNP) nanocomposites with well-dispersed GNPs were fabricated by in-situ shear exfoliation of graphite in SBS solution, followed by a co-precipitation process. The SBS macro-molecules were immobilized on the surfaces of exfoliated GNPs through π-π interaction, which not only prevented the exfoliated GNPs from restacking in the suspension, but also improved their dispersibility in SBS matrix. Thus, GNPs were uniformly dispersed in SBS/GNP nanocomposites and possessed strong interfacial adhesion with SBS, which formed efficient thermal conductive filler networks with reduced interfacial thermal resistance. Hence, at 14.7 vol% filler, SBS/GNP nanocomposites displayed an excellent thermal conductivity of 1.55 W m −1 K −1, which is 204% higher than SBS/commercial GNP (c-GNP) composites (0.51 W m −1 K −1 ) prepared by simply adding c-GNPs in SBS matrix. Moreover, SBS/GNP nanocomposites displayed enhanced tensile moduli and higher glass transition temperatures. Therefore, this work has provided a facile and promising route to manufacture high-performance TIMs in large scale.